INTERNALISASI AJARAN ISLAM MELALUI LAYANAN KONSELING DAN TERAPI BAGI WARGA BINAAN RUMAH TAHANAN NEGARA KELAS II B ANAK AIR PADANG - Zuwirda Zuwirda; Eliza Eliza; Nazirman Nazirman (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2018)
The Community Service Program of UIN Imam Bonjol Padang is a concrete implementation of scientific and religious studies organized by the academic community of UIN Imam Bonjol Padang for the Community. In the process of community service carried out by lecturers in coordination of LP2M and the Faculty of Da'wah and Communication Sciences of UIN Imam Bonjol Padang in 2017. So the group of lecturers of Islamic Counseling Guidance held community service activities with the title "Internalization of Islamic Teaching Through Counseling and Therapy Services Citizens Assisted in Class II B Prison for Air Children in Padang ". The actual actions of UIN Imam Bonjol Padang in an institutional and structured and routine manner in the field of religious social affairs which directly touched the community were quite good but on a certain side touched significantly. There are some problems faced by the community that seem to escape the attention of UIN Imam Bonjol Padang. The wider community really hopes that UIN Imam Bonjol Padang should be more active in preventing, maintaining and solving various community problems, especially in the field of socio-religious affairs and other fields that have relevance to the vision, the mission of UIN Imam Bonjol Padang.